Mittelalterliche Glasfingerringe mit ovalem Kopf: Insignien geistlicher Repräsentanten? - Wehner, Donat (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
Medieval glass rings appear in various social milieus. In the case of glass rings with oval plates, it is the representatives of spiritual life that appear to have been the bearers of such rings. This is supported by discoveries of rings with seal plates, yellow in colouring, and the large diameter of many of these rings which allows them to be worn over gloves, together with the presumed context of religious production, and last but not least, the discovery of these rings at sites with sacred connections.